Estimating heterogeneous agents behavior in a two-market financial system - Zhenxi Chen; Weihong Huang; Huanhuan Zheng (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
In this paper, we propose a two-market empirical model with heterogeneous agents based on Chiarella et al. (2012). Using monthly data of French and US stock markets, the regression shows that individual markets have feature of two-regime switching process. By including inter-market traders whose trading decision is based on fundamental value of foreign market, the two-market model has a better capability in explaining both markets with domestic fundamental traders turning to be significant. The existence of inter-market traders implies that the two markets impact each other through their fundamental and hence share some common set of factors, which provides foundation of market interactions, such as market co-movement.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: D84; G12; G15; 330; cross-correlation; co-movement; heterogeneous agents; financial multi-market interactions